Ответы и объяснения

2013-01-16T09:19:44+00:00
1. (3/7)^{3-2x} = (7/3)^{-6} (3/7)^{3-2x}= (3/7)^{6} 3-2x=6 X= -3/2= -0,6 2. (51/9)^{71(корня x-1)-3}= (51/9)^{-3(корня x-1) + 293 71(корня x-1)-3=-3(корня x-1)+293 74(корня х-1) = 296 (Корень х-1) = 4 Возводим в квадрат Х=16+1=17
2013-01-16T09:21:47+00:00

первый пример:

(3/7)^3-2x=(49/9)^-3

(3/7)^3-2x=(9/49)^3

(3/7)^3-2x=(3/7)^6

3-2x=6

-2x=6-3

-2x=3

x=-3/2

 

(51/9)^71корень(x-1)-3=(9/51)^3корень(х-1)-293

(51/9)^71корень(x-1)-3=(51/9)^-3корень(х-1)+293

71корень(x-1)-3=-3корень(х-1)+293

 71корень(x-1)+3корень(х-1)=293+3

74корень(х-1)=296 корень(х-1)=4

возыодим в квадрат уравнение

х-1=16

х=17